Experimental and Numerical Investigation of Gaseous Detonation in a Narrow Channel with Obstacles - Pavel N. Krivosheyev; Alexey O. Novitski; Kirill L. Sevrouk; Oleg G. Penyazkov; Ivan I. But; Aslan R. Kasimov (Fluids, 2021)
Gaseous detonation propagation in a thin channel with regularly spaced cylindrical obstacles was investigated experimentally and numerically. The wave propagation with substantial velocity deficits is observed and the details of its propagation mechanism are described based on experimental measurements of the luminosity and pressure and on three-dimensional flow fields obtained by numerical simulations. Both experiments and simulations indicate a significant role of shock–shock and shock–obstacle interactions in providing high-temperature conditions necessary to sustain the reaction wave propagation.